KEBIJAKAN BAZNAS KABUPATEN BANGKA DALAM MENGELOLA UMKM UNTUK MERUBAH MUSTAHIK MENJADI MUZAKKI - Tohari, Mustofa; Zahri, Tsulis Amiruddin; Sumar, Sumar (I-Economics, 2023)
Professional management of Zakat funds can be one way to eradicate poverty in society. One of the efforts made by the National Zakat Amil Agency (BAZNAS) of Bangka Regency, Bangka Belitung Islands Province in managing zakat funds is to distribute aid to Micro, Small and Medium Enterprises (MSMEs) through a productive zakat program. MSMEs have an important role in supporting the economy in Indonesia. Apart from that, MSMEs are also considered as a people's economic activity that is in accordance with the values of Pancasila as the nation's ideology. The aim of this research is to analyze and identify the management of BAZNAS Bangka Regency in managing the people's zakat funds through MSME activities. This research uses a qualitative-descriptive approach with primary data in the form of interviews and field observations and supported by secondary data in the form of literature relevant to the research topic. As a result, in carrying out the program BAZNAS Bangka Regency has three stages, namely open submission, field verification and evaluation monitoring. Recipients of MSME business funding assistance have the opportunity to receive it again the following year so that they can raise their social status from zakat recipients (Mustahik) to zakat payers (Muzakki). So the management of BAZNAS MSMEs is a form of mutual cooperation to realize community welfare as a reflection of the Pancasila economy